The Development of Rice Field Area in Special Region of Yogyakarta - Pratiwa Siregar, Abi; Oktaviana, Nadia; Rahmantyo Tarsilohadi, Edy (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
In general, the development of agricultural land usage change was illustrated through linear trend analysis without comparing it first with other trend analysis. As a consequence, it was assumed that the data will be in a straight line with a tendency for constant numbers over a period of time. However, the facts on the ground proved that the area of ??agricultural land converted into non-agricultural land was not always the same from year to year. The novelty of this research was to do a comparison between linear and non-linear trends to predict the development of rice fields, so that an accurate forecasting model was obtained. The aim of this research were: 1) knowing the development of rice fields area in the Special Region of Yogyakarta, 2) determining the appropriate forecasting model for the development of rice fields area in the Special Region of Yogyakarta, and 3) forecasting the area of ??rice fields in the Special Region of Yogyakarta. The data that used came from BPS (Central Bureau of Statistics) from 1996 to 2017. The trend models being compared were linear trends, quadratic trends, and exponential trends. The results showed that the area of ??rice fields in the Special Region of Yogyakarta tended to decrease from year to year. The best forecasting model was an exponential trend. In 2017 to 2021, it was estimated that there will be a decrease in rice field area of ??221 hectares or 0.41 percent per year.